Problem Solving Learning Model as an Alternative to Mathematics Learning that Can Foster Student Learning Independence at SMK Panca Budi - Nina Fadilah; Fitri Ayu; Mira Yosefa Siregar; Desi Ramadhani (International Forum of Researchers and Lecturers, 2024)
The Problem-Solving Learning Model is one of the learning models that can develop problem-solving skills and student learning independence where this model is developed based on polya theory known as problem-solving steps, namely: identifying problem information/understanding problems, planning problem-solving strategies, using problem-solving strategies and re-examining solutions or solutions to problems that have been generated. The Use of the Problem-Solving Learning Model to Improve the Problem-Solving Ability of Pancabudi Private Vocational School Students for the 2023/2024 Academic Year. The purpose of this research is to determine the effectiveness of learning using the Problem-Solving learning model. This research is located at SMK Swasta Pancabudi where the class applies the Problem Solving learning model which will be compared with different classes using the classical learning model.